Effect Of First Aid Training For Child Experiencing Choking On The Knowledge And Skill In Carrying Out Abdominal Thrust In Integrated Kindergarten Of Madani Palu - Hasnidar; Sukrang; Fauzan; MA Munir (Comprehensive Health Care, 2023)
Choking is an emergency incident or situation that often occurs in society. Choking is caused by a foreign object entering the respiratory tract. Knowledge about handling choking incident will affect people's behavior in handling choking incident and avoiding its death threat to children. One of the efforts to increase public knowledge concerning this matter is training in First Aid for Choking Incident on Children. This research is a Pre-Experimental study with a one group pretest posttest design. The population in this study is all teachers, staff, and parents or families of the students of Madani Integrated Kindergarten of Palu who were at Madani Integrated Kindergarten of Palu. In this case, the sample involved was 47 patients, who were selected using the accidental sampling method. Furthermore, hypothesis test of paired T-test was carried out using a significance level of p<0.05. Based on the research results, it was found that there was a significant effect of providing first aid training to children experiencing choking on increasing knowledge and skills in performing Abdominal Thrust at Madani Integrated Kindergarten in Palu with P Value of 0.000 (< α 0.05). Therefore, it can be concluded that there is an influence of providing first aid training to children experiencing choking on increasing knowledge and skills in performing Abdominal Thrust. It is further expected that the community, especially parents, teachers and school staff, can improve their ability to provide first aid to children experiencing choking so that deaths due to choking can be prevented. Keywords: first aid for choking, Abdominal Thrust